2017
DOI: 10.1093/dote/dox036
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalated neoadjuvant chemoradiotherapy with dose-painting intensity-modulated radiation therapy and improved pathologic complete response in locally advanced esophageal cancer

Abstract: We compared pathologic complete response (pCR) rate, toxicity, and postoperative complications between patients treated preoperatively with 50.4 Gy versus dose escalation with dose-painting intensity-modulated radiation therapy (dp-IMRT) to 56 Gy in locally advanced esophageal cancer. We evaluated esophageal cancer patients treated between 2006 and 2014 with preoperative IMRT chemoradiation to a dose of 50.4 Gy versus 56 Gy. The endpoints were pCR and toxicity. We identified 113 patients (50.4 Gy: n = 40; 56 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…In our selected population, we observed pCR in 34 (50%) patients following NACRT, which is in accordance with published reports 1–3,5 . The CROSS study reported pCR rates of 29% with a radiation dose of 41.4 Gy.…”
Section: Discussionsupporting
confidence: 92%
“…In our selected population, we observed pCR in 34 (50%) patients following NACRT, which is in accordance with published reports 1–3,5 . The CROSS study reported pCR rates of 29% with a radiation dose of 41.4 Gy.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with our results. On the other hand, a study published in 2017 showed a higher rate of local control with no increase in therapy-related toxicity [32].…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with our results. On the other hand, a study published in 2017 showed a higher rate of local control with no increase in therapy-related toxicity [32]. The literature published so far proclaims the need of further studies especially with regard to improved radiation techniques, tumor histology, tumor localization, therapeutic alternatives, and salvage options in cases of local failure, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized phase-III studies compared definitive CRT and preoperative CRT followed by surgery and did not find a statistical significant OS benefit in favor of the additional surgery but an increased number of loco-regional recurrences in the organ preservation arm 6 , 7 . After preoperative CRT tumor specimens of up to 20% of patients do not show major signs of regression 2 , these patients would be candidates for alternative treatment approaches that might comprise immediate surgery, checkpoint inhibition, image based radiation dose escalation or other 8 12 .…”
Section: Discussionmentioning
confidence: 99%